Role of Microfinance in Entrepreneurial Development of Women in India - Yasar Imam; Prof. Anwar Khurshid Khan (HM Journals, 2021)
Today, one of the most widely debated topics in the world is disparity in global wealth and access to social services. Within the new economy, microfinance is becoming a more powerful tool for poverty alleviation. The bulk of microfinance programs were established with the explicit objective of alleviating poverty and empowering individuals of the country. Furthermore, a rising number of microfinance institutions (MFIs) prefer to work with promising entrepreneurs with unique business ideas because they believe they are more responsible and trustworthy. Programs such as the Self Help Bank Linkage Program in India have been steadily gaining popularity due to their beneficial economic impact and the assumption that they help women to become more self-sufficient. So far, the SHG Program has delivered microfinance to its mostly female participants using a new form of group saving and lending. According to the research, investing in women has been proved to be the most effective way to increase family health, nutrition, hygiene, and educational levels, and hence the entire society. Thus, it is vital to provide additional support for women in both financial and non-financial services. A large number of top public and private sector banks are launching programs specifically aimed to assist women in starting their own businesses. In recent years, even the unorganized sector has begun to participate in the microfinance movement. The purpose of this study is to determine the effectiveness of microfinance as a tool for boosting women entrepreneurship in India.